2017
DOI: 10.1002/jemt.22961
|View full text |Cite
|
Sign up to set email alerts
|

A novel classification scheme to decline the mortality rate among women due to breast tumor

Abstract: Early screening of skeptical masses or breast carcinomas in mammograms is supposed to decline the mortality rate among women. This amount can be decreased more on development of the computer-aided diagnosis with reduction of false suppositions in medical informatics. Our aim is to provide a robust tumor detection system for accurate classification of breast masses using normal, abnormal, benign, or malignant classes. The breast carcinomas are classified on the basis of observed classes. This is highly dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…About 1.59 million people died of lungs cancer in 2012 alone and that accounts for approximately 27% of all cancer‐related deaths (McGuire, ). A study of American Cancer Society has revealed that lung cancer‐related deaths are even higher than the sum of deaths caused by other prevalent cancer types like breast and prostate (DeSantis, Ma, Bryan, & Jemal, ; Mughal, Muhammad, Sharif, Saba, & Rehman, ; Mughal, Sharif, Muhammad, & Saba, ).…”
Section: Introductionmentioning
confidence: 99%
“…About 1.59 million people died of lungs cancer in 2012 alone and that accounts for approximately 27% of all cancer‐related deaths (McGuire, ). A study of American Cancer Society has revealed that lung cancer‐related deaths are even higher than the sum of deaths caused by other prevalent cancer types like breast and prostate (DeSantis, Ma, Bryan, & Jemal, ; Mughal, Muhammad, Sharif, Saba, & Rehman, ; Mughal, Sharif, Muhammad, & Saba, ).…”
Section: Introductionmentioning
confidence: 99%
“…Before resolving the contrast problem, first hairs from lesion area are removed because hairs on the lesion area affect the segmentation of lesion. In literature, many methods have been implemented for hair removals (Kasmi & Mokrani, ; Lee, Ng, Gallagher, Coldman, & McLean, ; Mirzaalian, Lee, & Hamarneh, ; Mughal et al, ,b,c). In this research work, the improved DullRazor technique (Kiani & Sharafat, ) is utilized, which work better as compared to Lee et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Most of the reported techniques focused to resolve issues of image luminance, low contrast, negative illumination, and out of focus images in the pre‐processing step. The most of the reported techniques employed pre‐processing steps histogram equalization (HE; Purwar, Shah, Clarke, Almugairi, & Muehlenbachs, , Mughal et al, ,b; Sheeba, Thamburaj, Mammen, & Nagar, ), brightness preserving dynamic HE (BPD) (Mandal, Kumar, Chatterjee, Manjunatha, & Ray, ), smallest uni‐fee phase assimilating nucleus (Smith & Brady, ) smoothing the image via Median clear out an area renovation via Laplacian (Savkare & Narote, ) and within the equal way, however for aspect renovation, some researchers employed un‐sharp masking (Mohapatra & Patra, ; Mohapatra, Patra, & Kumar, ; Mohapatra, Samanta, Patra, & Satpathi, ). The underlying study considered image smoothing through the median filter of kernel size (3 × 3), high kernel size will remove the parasites, particularly at initial stages.…”
Section: Related Workmentioning
confidence: 99%